2018
DOI: 10.4194/1303-2712-v18_1_08
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Protein hydrolysates from skipjack tuna viscera prepared using Alcalase 2.4 L (VPH) with different degree of hydrolysis (DH: 10%, 20% and 30%) were prepared and determined for their antioxidative activity. VPH with 20% DH had the highest DPPH, ABTS radical scavenging activities and ferrous chelating activity (P<0.05). However, ferric reducing antioxidant activity of hydrolysates increased as DH increased (P<0.05). When VPH with 20% DH was determined for its pH and thermal stability, ABTS radical scavenging act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Nevertheless, the α-AIA and α-GIA stability of these samples gradually decreased as the pH shifted to very low or very high values (Figure 4). This could be due to the changes in the charges of peptides, particularly at the N-and C-terminus at high acidic and alkaline conditions [78], altering the electrostatic interactions and hydrogen bonds and transforming their secondary structures and solubility, resulting in the loss of bioactivity [79,80]. The change in the stability of these samples could be due to the impact of pH on one particular or more amino acids.…”
Section: Investigation Results Of Thermal and Ph Stability Of α-Aia A...mentioning
confidence: 99%
“…Nevertheless, the α-AIA and α-GIA stability of these samples gradually decreased as the pH shifted to very low or very high values (Figure 4). This could be due to the changes in the charges of peptides, particularly at the N-and C-terminus at high acidic and alkaline conditions [78], altering the electrostatic interactions and hydrogen bonds and transforming their secondary structures and solubility, resulting in the loss of bioactivity [79,80]. The change in the stability of these samples could be due to the impact of pH on one particular or more amino acids.…”
Section: Investigation Results Of Thermal and Ph Stability Of α-Aia A...mentioning
confidence: 99%
“…The FRAP assays of ATC and VTC were not significantly different ( p > 0.05), but these two collagens showed a higher FRAP value than APTC ( p ≤ 0.05). The stronger reduction powder indicated that it could donate an electron to free radicals, resulting in a capacity to prevent or retard in the state of propagation [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…The emulsifying activity index (EAI) and emulsion stability index (ESI) were used to measure the emulsification of PPIs and PPI-polysaccharide complexes by the procedure described by Klomklao & Benjakul. [20] Arachis oil (3 ml) and sample solutions (1%, 9 mL, fresh samples) were homogenized (Model T25 basic; IKA-Labortecnik, Selangor, Malaysia) at a speed of 12,000 rpm for 1 min. The 20 μL emulsion was quickly taken from the bottom of the emulsion and added to a 0.1% (w/v, 5 mL) sodium dodecyl sulfate (SDS) solution and shaken well.…”
Section: Emulsifying Activity Index (Eai) and Emulsion Stability Index (Esi)mentioning
confidence: 99%
“…[26] The interaction between proteins and polysaccharides in food systems can show better performance than either used independently and can affect the flavor, nutrition, texture, and other qualities of the food system. [20] The solubility of PPIs and PPI-polysaccharide complexes is presented in Figure 2. The solubility of PPIs was (7.68 ± 0.54%), and compared to that of PPIs, the solubility of the complexes changed to different degrees.…”
Section: Solubilitymentioning
confidence: 99%